An Analysis of Grammatical Errors in English Speech by a Turkish YouTuber in EFL Context - Putri Aprilia Pasaribu; Rahmat Huda; Salsa Putri; Nur Kaidah Sitompul; Rini Elvri; Suraida (jurnalalfa, 2026)
This research is intended to examine common grammatical errors found in the English speech produced by a Turkish YouTuber, Handeyavz, in her video entitled “Cozy Travel Vlog” within the context of English as a Foreign Language (EFL). The study is based on the issue that many EFL learners can speak English fluently but still frequently make grammatical mistakes, especially during spontaneous communication. This phenomenon raises concerns regarding the relationship between fluency and grammatical accuracy in spoken English. Therefore, the research aims to identify the types of grammatical errors produced by the speaker and explore the factors contributing to those errors. This study applies a qualitative descriptive method using a content analysis approach. The data were gathered through documentation techniques by selecting the video, repeatedly observing it, and transcribing the speaker’s utterances into written text. After that, the data were analysed through several stages, including error identification, classification, description, and explanation. The results reveal that the most frequent grammatical errors involve subject-verb agreement, incorrect tense forms, omission of articles, and inappropriate use of prepositions.